Comparison of the activity profile during Grand Slam women`s doubles tennis - Borderias, M.; Fernandez-Fernandez, J.; Martínez-Gallego, R.; Baiget, E. (International Journal of Performance Analysis in Sport, 2021)
There is little information on the female doubles tennis. The aim of this study was to describe the activity profile of women`s doubles tennis, and to analyse the differences between playing surfaces. Twenty-one matches of three Grand Slams (GS) tournaments and played on 3 different surfaces, were analysed. Activity profile included rally duration (RD), resting time between points (RTP), resting time between games (RTG), resting time between sets (RTS), resting time (RT), effective playing time (EPT), total match time (TMT), work-to-rest ratio (W: R), shots per rally (SPR), shots per game (SPG), shots per set (SPS), shots per match (SPM), shot frequency (shots/second) (SPSc), and type of shots. Results showed that RTG and RT was longer at the Australian Open than at Roland Garros and Wimbledon, and the number of forehand (F) shots at Roland Garros was higher than at Wimbledon. The most common tennis shots are the F, the backhand (B), the first service and the volley (V), and more than 50% of the total shots in a match come from the baseline and mid court game. These results show that in women`s doubles the stimuli are short and intense and that net game is very important.